Pengaruh Arrogance, Competence, Opportunity, Pressure dan Rationalization Terhadap Tindakan Kecurangan Pengelolaan Keuangan Badan Usaha Milik Desa (BUMDES) di Kecamatan Gerokgak - I Komang Widiantara; I Gede Putu Banu Astawa (Universitas Pendidikan Ganesha, 2022)
This research aimed to obtain empirical evidence of the effect of arrogance, competence, opportunity, pressure and rationalization on fraudulent financial management at BUMDes in Gerokgak District. This study was a quantitative causality study using primary data obtained from questionnaires and measured using a likert scale. The population of this research were all BUMDes in Gerokgak District as many as 12 BUMDes. The sampling technique used purposive sampling technique and the amount of research samples obtained was 11 BUMDes with 44 respondents. The data analysis technique used multiple linear regression analysis. The results of this study indicate that partially arrogance, competence, opportunity, pressure and rationalization had a positive effect on fraudulent financial management at BUMDes in Gerokgak District.